Peran social media marketing gabag indonesia dalam mempertahankan brand equity pada pandemi covid-19 - Azizah, Sarah (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
This study discusses the role of Gabag Indonesia's social media marketing in maintaining brand equity in the Covid-19 pandemic. The problem of this research is that the Covid-19 pandemic that occurred in Indonesia has caused many losses to the existing business and economic sectors and the cessation of direct sales, especially in the retail sector, and forcing brands to carry out activities online, namely through social media. The formulation of the problem in this study is how the role of social media Marketing for Gabag Indonesia in maintaining brand equity in the Covid-19 pandemic? Qualitative descriptive research method is used to analyze the problems that exist in this study. The conclusion of this study is the importance of the role of Social Media Marketing of Gabag Indonesia in maintaining brand equity during the Covid-19 pandemic.Â Keywords: Pandemic; Covid-19; Social Media; Marketing, Brand Equity.Â